(untitled) (Al-Academy, 2025)
The environmental implications stage is an important stage in which societies change and develop, providing them with the experiences, skills, and beliefs that play an effective role in achieving intellectual and cognitive values. At the forefront of these tools are theatrical texts that address the environmental theme and the form of culture that can be added to it. The study consisted of an introduction, which addressed the role of theatre in protecting environmental issues, a cultural act that relies on raising awareness to mitigate the seriousness of these issues. The researcher also defined the problem of her study, represented by the following question: What are the transformations of contemporary theatre in the environment and the functions that touch on sustainable culture? Her goal in answering this question is to identify the role of theatre in environmental issues through a culture of sustainability. The importance of the research also lies in identifying the levels of employment of artistic actions within the realm of theatrical art. The theoretical framework, which consisted of three parts, included the first: the concept of environmental theatre; the second: the concept of culture and environmental awareness; and the third: the intellectual and behavioural dimensions of environmental implications in sustainable theatre culture. The researcher then reviewed the procedures used in the research sample, the play "The Towers and the Wind," written and directed by Theiser Renjevo. To complete the set of results and conclusions that came as a continuation of the researcher’s study, the researcher then identified the recommendations and suggestions related to the study’s results and then concluded her study with the sources that were adopted.